Molecular mechanisms underlying chemopreventive potential of butein: Current trends and future perspectives. (1st December 2021) - Tuli, Hardeep Singh; Joshi, Ruchira; Aggarwal, Diwakar; Kaur, Ginpreet; Kaur, Jagjit; Kumar, Manoj; Parashar, Nidarshana Chaturvedi; Khan, Md Asaduzzaman; Sak, Katrin
Abstract: Despite extensive efforts, cancer is still often considered as an incurable disease and initiation of novel drug development programs is crucial to improve the prognosis and clinical outcome of patients. One of the major approaches in designing the novel cancer drugs has historically comprised studies of natural agents with diverse anticancer properties. As only a marginal part of natural compounds has been investigated, this approach still represents an attractive source of new potential antitumor molecules. In this review article, different anticancer effects of plant-derived chalcone, butein, are discussed, including its growth inhibitory action, proapoptotic, antiangiogenic and antimetastatic activities in a variety of cancer cells. The molecular mechanisms underlying these effects are presented in detail, revealing interactions of butein with multiple cellular targets (Bcl-2/Bax, caspases, STAT3, cyclins, NF-κB, COX-2, MMP-9, VEGF/R etc.) and regulation of a wide range of intracellular signal transduction pathways. These data altogether allow a good basis for initiating further in vivo studies as well as clinical trials. Along with the efforts to overcome low bioavailability issues generally characteristic to plant metabolites, butein can be considered as a potential lead compound for safe and more efficient cancer drugs in the future. Highlights: Butein, a bioactive plant-derived chalcone with promising therapeutic applications. Induction of apoptosis and cell cycle arrest in cancer. Inhibition of tumour neo-vasculature and metastasis. Butein mediated redox and anti-inflammatory properties. Synergistic and nano delivery of butein against cancer.